Smell and taste dysfunction during the COVID-19 outbreak: a preliminary report - Gelardi, Matteo; Trecca, Eleonora; Cassano, Michele; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
In late December 2019, in Wuhan (China), health authorities reported several clusters of pneumo- nia of unknown cause, subsequently attributed to a novel coronavirus, identified as Severe Acute Respiratory Syndrome-Coronavirus 2. Anosmia and dysgeusia have been reported as particular symptoms.4,5  Notably, these sensory symptoms seem to have a peculiar trend, such as usually precede the onset of respiratory symp- toms. So, they have been defined as “sentinel” symptoms. We presented a series of COVID-19 patients. Anos- mia and dysgeusia frequently preceded respiratory complaints. Anosmia and dysgeusia seem to be short-lived and self-resolving in COVID-19, thus a neurotoxic effect swiftly disappearing and/or cytopathic damage could be hypothesized similarly to other viral infections.